2022
DOI: 10.3390/jof8050430
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiles Elucidate Differential Host Responses to Infection with Cryptococcus neoformans and Cryptococcus gattii

Abstract: Many aspects of the host response to invasive cryptococcal infections remain poorly understood. In order to explore the pathobiology of infection with common clinical strains, we infected BALB/cJ mice with Cryptococcus neoformans, Cryptococcus gattii, or sham control, and assayed host transcriptomic responses in peripheral blood. Infection with C. neoformans resulted in markedly greater fungal burden in the CNS than C. gattii, as well as slightly higher fungal burden in the lungs. A total of 389 genes were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
(78 reference statements)
1
4
0
Order By: Relevance
“…Substantial dissemination to the spleen and the brain occurred only for KN99-infected groups, and this was most pronounced at 21 DPI ( Figure 1E ). These trends agree with published data ( 6 , 29 , 30 , 32 , 33 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Substantial dissemination to the spleen and the brain occurred only for KN99-infected groups, and this was most pronounced at 21 DPI ( Figure 1E ). These trends agree with published data ( 6 , 29 , 30 , 32 , 33 ).…”
Section: Resultssupporting
confidence: 93%
“…Differences between C. neoformans H99 and C. gattii R265 infections in unvaccinated mice have been well-characterized in the literature ( 6 , 29 33 ). While experimental models of cryptococcosis can vary by mouse background and inoculation method, studies from multiple research groups highlight the following consensus phenotypes for each fungal strain: i) In models of pulmonary infection, there are no significant differences in survival comparing mice infected with H99 versus R265 ( 6 , 29 , 30 ), ii) H99 disseminates more readily from the lungs than R265 ( 29 , 32 ), iii) immune cell infiltration of the lungs is much less with R265 infection ( 6 , 30 , 31 ), and iv) H99 induces greater levels of Th1 and Th17 cytokines in the lungs ( 6 , 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Classically activated M1 macrophages that result from the usual Th1 cytokine immune profiles are essential for clearing Cryptococcus, while alternatively activated M2 macrophages resulting from Th2 cytokine stimulation are associated with a higher burden of disease [ 52 , 53 ]. C. gattii can modulate macrophage polarisation to M2, thereby evading immune recognition and clearance [ 51 , 52 , 53 ]. There are observed species-dependent in vitro differences in M1-polarised macrophage transcriptomic gene regulation and subsequent bioprocess modulation.…”
Section: Advances In Understanding Of Virulence and Pathogenesismentioning
confidence: 99%
“…Both species elicit a robust host immune response. However, murine studies note a considerably different species-dependent host transcriptomic profile [ 52 ]. There is variation in the molecular and chemical properties of extracellular enzymes secreted by C. gattii compared with C. neoformans , perhaps reflecting their different environmental niches and contributing to different clinical manifestations [ 57 ].…”
Section: Advances In Understanding Of Virulence and Pathogenesismentioning
confidence: 99%
“…Other than this pathway, the inflammatory response caused by heat-killed C. neoformans and C. gattii seem to be distinct from each other. A transcriptomics study that infected mice using both C. neoformans a nd C. gattii , also identified distinct gene expression signatures caused by the two fungal species, but they were not entirely unique [27]. Although there were differences, the study also found classical complement activation as unique to C. gattii infection, compared to C. neoformans , and expression of natural killer cell genes, such as receptor KIR2DL4 , unique to C. neoformans .…”
Section: Discussionmentioning
confidence: 99%